Public management reform: a comparative analysis into the age of austerity - Pollitt, Christopher; Bouckaert, Geert (Oxford, 2017)
The most authoritative, comprehensive, widely-cited academic text on public management reform in Europe, North America and Australasia.
Keywords: Public Management